THE EFFECT OF ECONOMIC OPENNESS ON INCOME INEQUALITY AT THE PROVINCE LEVEL IN INDONESIA - Hasna, Hanifa Tsuny (Jurnal Ekonomi, 2020)
This study aims to determine the effect of economic openness which is divided into export openness, import openness, and foreign investment openness on income inequality at the provincial level in Indonesia. The estimation method used is the fixed effect method. The data used is panel data from 29 provinces in Indonesia. Based on the results of the analysis, it was found that only export openness had a significant effect on reducing income inequality at the provincial level in Indonesia, while import openness and foreign investment openness had no significant effect.